The Relationship of Body Length and Width of Karakul Lambs - Mamatov Bakhtiyor Salimovich; Akbarova Maxliyo Vafoevna (Zien Journals, 2022)
The article highlights the results of studies to determine the boundaries of the influence of body size on the length and width of curls of the Karakul lambs.
Keywords: Karakul sheep; lambs; Karakul skins; body size